Penerapan Business Judgement Rule Terkait Dengan Keputusan Direksi PT BUMN - Sudarna, Sudarna (Lex Stricta : Jurnal Ilmu Hukum, 2025)
The decision of the board of directors in managing the company related to its core business is required to be able to manage the company with good integrity, full of caution, in order to obtain profits. Directors running the company's activities can prove that the decisions taken are not based on personal interests but for the benefit of the company. BUMN companies in carrying out their business are not only in the field of private law, but their business is also carried out in the field of public law.  The purpose of this research is to find out whether the new BUMN Law can create impunity loopholes, especially in cases of corruption that are neatly structured within BUMN. The results showed that BUMN companies not only run the core business, but are also given the mandate to carry out government functions to provide public services or as PSO implementers such as subsidized fertilizers to support food self-sufficiency programs.  As a PSO Executor, it is certainly oriented in handling direct state financial flows, for that there must be administrative separation and its implementation must be open. if studied administratively and referring to Law Number 28 of 1999, this policy cannot be ignored, even so the directors are included as State Officials. Why is this so, directors can be convicted in corruption cases if the elements of state losses are met, if proven negligent in making decisions that have an impact on state losses. In the new BUMN Law, directors are given the freedom to manage the company through the principle of Business Jugement Rule, this principle does not mean that the actions of directors become immune to the law or cannot be a shield for corrupt practices that harm the state.